2016
DOI: 10.1017/s0022377816000957
|View full text |Cite
|
Sign up to set email alerts
|

Multi-D magnetohydrodynamic modelling of pulsar wind nebulae: recent progress and open questions

Abstract: In the last decade, the relativistic magnetohydrodynamic (MHD) modelling of pulsar wind nebulae, and of the Crab nebula in particular, has been highly successful, with many of the observed dynamical and emission properties reproduced down to the finest detail. Here, we critically discuss the results of some of the most recent studies: namely the investigation of the origin of the radio emitting particles and the quest for the acceleration sites of particles of different energies along the termination shock, by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
104
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(108 citation statements)
references
References 135 publications
4
104
0
Order By: Relevance
“…This feature has been observed by now in a number of PWNe, among which the Crab nebula (Weisskopf et al 2000), Vela (Helfand, Gotthelf & Halpern 2001;Pavlov et al 2001) and MSH 15-52 (Gaensler et al 2002;DeLaney et al 2006), to name just a few. It is now commonly accepted that this structure arises due to the interplay of the anisotropic energy flux in the wind with the toroidal magnetic field, as confirmed by a long series of numerical simulations (Komissarov & Lyubarsky 2003Del Zanna, Amato & Bucciantini 2004;Del Zanna et al 2006;Volpi et al 2007;Camus et al 2009;Porth, Komissarov & Keppens 2014;Olmi et al 2014Olmi et al , 2016. In general, two dimensional models are built on the axisymmetric assumption of a purely toroidal magnetic field, while three dimensional models have usually much lower resolution, and can only ⋆ E-mail: niccolo@arcetri.astro.it investigate large scale deviations from axisymmetry.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…This feature has been observed by now in a number of PWNe, among which the Crab nebula (Weisskopf et al 2000), Vela (Helfand, Gotthelf & Halpern 2001;Pavlov et al 2001) and MSH 15-52 (Gaensler et al 2002;DeLaney et al 2006), to name just a few. It is now commonly accepted that this structure arises due to the interplay of the anisotropic energy flux in the wind with the toroidal magnetic field, as confirmed by a long series of numerical simulations (Komissarov & Lyubarsky 2003Del Zanna, Amato & Bucciantini 2004;Del Zanna et al 2006;Volpi et al 2007;Camus et al 2009;Porth, Komissarov & Keppens 2014;Olmi et al 2014Olmi et al , 2016. In general, two dimensional models are built on the axisymmetric assumption of a purely toroidal magnetic field, while three dimensional models have usually much lower resolution, and can only ⋆ E-mail: niccolo@arcetri.astro.it investigate large scale deviations from axisymmetry.…”
Section: Introductionmentioning
confidence: 91%
“…In the past years several models have been presented to simulate the X-ray emission map of PWNe (with a particular focus on Crab): ranging from simplified toy-models (Ng & Romani 2004;Schweizer et al 2013), to more complex multi-dimensional time-dependent simulations (Volpi et al 2007;Porth, Komissarov & Keppens 2014;Olmi et al 2016). Starting from the early work of Bucciantini et al (2005), polarization have also been modelled using in general a magnetic field geometry derived from numerical simulations (Del Zanna et al 2006;Porth, Komissarov & Keppens 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These jets can be launched shortly after the explosion or a long time after, e.g., in a PWN. For example, in a recent paper Olmi et al (2016) conducted a 3D simulation of a PWN and demonstrated the formation of jets. In all three scenarios the jets are not active during the SNR phase, unless a close binary companion transfers mass to the compact remnant (see below).…”
Section: The Relation Between Jets and Earsmentioning
confidence: 99%
“…Of course in terms of reproducing both the spectrum and the morphology what is needed is a reorganisation of the field, rather than simple dissipation, so as to decrease the field tension while still keeping its strength. Long duration simulations [40,48], in which an asymptotic self-similar solution appears to be fully reached, show that after an initial phase of continuous decrease, the average field strength reaches a constant value. However, up to now no simulation is available that can fully reproduce both the morphology and SED of the Crab Nebula.…”
Section: Lessons From Multi-d Mhd Simulationsmentioning
confidence: 96%
“…In particular, the value of σ that best reproduces the nebular morphology fails to reproduce the multi-wavelength spectrum of the Crab Nebula: the average value of the nebular magnetic field is too low, and as a consequence, if one considers injection of a sufficiently large number of particles, so as to reproduce the high energy synchrotron spectrum, the Inverse Compton emission is largely overestimated. On the other hand, larger values of σ lead to exceedingly large hoop stresses: too large a fraction of the flow is diverted towards the pole and the equatorial emission is too faint [40].…”
Section: Lessons From Multi-d Mhd Simulationsmentioning
confidence: 99%